Acculturation and Re-entry Culture Confrontation: the Case of Development Workers - Petia Genkova; Johanna Pollinger (Journal of International Migration and Integration, 2021)
The study at hand investigated the reintegration of development workers in terms of the sociocultural adaption and societal engagement after the return to the home country. The investigation had a cross-sectional design with 311 returned development workers. The results show that the sociocultural adaption of development workers several years after their return was significantly related to their job-related personality. However, there were no group differences for cultural distance. Results indicate that individuals who are more actively working together with others might be more likely to readapt well after return. Moreover, the results show that experienced social appreciation of the stay abroad is a relevant predictor of further engagement. Considering that appreciation is very likely to be a central motive for development workers, this underlines the importance for organizations to worship the engagement of repatriating development workers by offering support as well as by creating a culture in which extraordinary engagement is honored sufficiently.
Keywords: 300; Expatriates; Homecoming; Reintegration; Development work; Societal engagement